The effect of biochar, cocopeat and sawdust compost on the growth of two dipterocarps seedlings - MARJENAH MARJENAH; KISWANTO KISWANTO; SRI PURWANTI; FENNY PUTRI MARIANI SOFYAN (Smujo International, 2016)
Abstract. Marjenah, Kiswanto, Purwanti S, Sofyan FPM. 2016. The effect of biochar, cocopeat and sawdust compost on the growth of two dipterocarps seedlings. Nusantara Bioscience 8: 39-44. Good growing media contains enough nutrients, light textured, and have the capacity to hold water to create conditions that can support plant growth. The growing media used for propagation has several requirements, that is firm and dense to enhance the growth of stems, has the capability to hold water, guarantee the plant life, and moderate humidity. This study attempts to evaluate the effect of biochar, cocopeat, and sawdust compost on the growth of Dryobalanops aromatica and Shorea balangeran seedlings. An experiment was conducted by using completely randomized block design (CRBD) in factorial with two factors, namely growing media (topsoil 100%? topsoil 80% + sawdust compost 20%? topsoil 80% + biochar 20%, topsoil 80% + 20% coco peat ) and two species of dipterocarps seedlings (D. aromatica and S. balangeran). The experiment was carried out in a Forestry Faculty nursery for 3 months. To determine the best growth media, the vegetative parameters of seedlings were measured and the data were statistically analyzed. Survival rates of both seedlings showed good specification in all types of growing media. The survival rates of D. aromatica for 100% topsoil (control)? 80% top soil+ 20% sawdust compost? 80% topsoil + 20% biochar? 80% topsoil + 20% cocopeat are 100%? 100%? 97.78% and 97.78%? respectively. S. balangeran are 93.33%? 100%? 100%? 97.78%. Quality Index of D. aromatica 100% topsoil (control)? 80% top soil+ 20% sawdust compost? 80% topsoil + 20% biochar? 80% topsoil + 20% cocopeat that are 0.15? 0.14? 0.10? and 0.10? and for S. balangeran 0.09? 0.38? 0.05 and 0.07 respectively.